Game + design education proceedings of PUDCAD 2020 - Cordan, Özge; Dinçay, Demet Arslan; Toker, Çağıl Yurdakul; Öksüz, Elif Belkıs; Semizoğlu, Sena (Springer Series in Design and Innovation, 2021)
This book gathers the papers of the PUDCAD Universal Design Practice Conference: Game + Design Education, organized by Istanbul Technical University and held online on June 24-26, 2020. The conference represented one of the key events of the Practicing Universal Design Principles in Design Education through a CAD-Based Game (PUDCAD) project, which developed a design game on a CAD-based platform, enabling students and designers to learn about universal design principles and develop accessible and innovative design ideas. As such, the PUDCAD project met one of the foremost goals of the European Commission, making sure the inclusion and efficient accessibility for people with disabilities into everyday life. The main topics of the conference include: universal design and education, universal design and user experience, game and design studies, gamification, virtual reality experiment, e-learning in design, and playful spaces and interfaces. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaboration among different specialists.